Awareness regarding infertility among women attending Chitwan fertility center - Dhakal, Radha Devi; Lamsal, Yasoda; Paudel, Dipesh (Journal of Chitwan Medical College, 2020)
Background: Infertility is a condition where couple failure to conceive after 1 year of regular unprotected coitus. At least 50 million couples worldwide experience infertility. Several adverse consequences of infertility like tension, hostility, anxiety, depression, self-blame and suicidal ideation are now being increasingly recognized. This study was designed to assess the awareness regarding infertility among women attending Chitwan Fertility Center. Methods: A cross sectional analytical study design was used and population for study includes those married women who had failure to conceive and visited to Chitwan infertility centre. The data was collected through semi-structured interview schedule. Collected data was coded and entered and analyzed in Microsoft office Excels and SPSS 20 version by using descriptive and inferential statistics. Results: In present study, among 96 respondents, majority of the respondents 45.8% were from age group of 25-30 years. Most of the respondents 56.3% had completed bachelor level and above level education. Majority of women 87.5% had good awareness on infertility. There was no significant association between level of awareness and socio-demographic variables. Conclusions: It can be concluded that the awareness about infertility among the participants attending Chitwan fertility center is relatively good. Most of the participants were educated, duration of marriage was also 5-10years and most of them came to the infertility center for the treatment and management of infertility that might be the reason they have good awareness regarding infertility. But there is still misconception in some of the participants.